In Silico and In Vitro Evaluation of Bevacizumab Biosimilar MB02 as an Antitumor Agent in Canine Mammary Carcinoma - Cardama, Georgina Alexandra (2023)
Canine mammary carcinomas (CMC) are associated with major aggressive clinical behavior and high mortality. The current standard of care is based on surgical resection, without an established effective treatment scheme, highlighting the urgent need to develop novel effective therapies. Vascular endothelial growth factor (VEGF) is a key regulator of tumor angiogenesis and progression in the majority of solid cancers, including human and canine mammary carcinomas. The first therapy developed to target VEGF was bevacizumab, a recombinant humanized monoclonal antibody, which has already been approved as an anticancer agent in several human cancers. The goal of this work was to establish the therapeutic value of MB02 bevacizumab biosimilar in CMC. First, through different in silico approaches using the MUSCLE multiple-sequence alignment tool and the FoldX protein design algorithm, we were able to predict that canine VEGF is recognized by bevacizumab, after showing an extremely high sequence similarity between canine and human VEGF. Further, by using an ELISA-based in vitro binding assay, we confirmed that MB02 biosimilar was able to recognize canine VEGF. Additionally, canine VEGF-induced microvascular endothelial cell proliferation was inhibited in a concentration-dependent manner by MB02 biosimilar. These encouraging results show a high potential for MB02 as a promising therapeutic agent for the management of CMC.